1991
DOI: 10.1023/a:1015862603939
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Proteolytic enzyme inhibitors were examined as absorption enhancers for the nasal delivery of vasopressin (AVP) and desmopressin (1-d-8-DAVP) in rats. Aprotinin, soybean trypsin inhibitor, and camostat mesilate were used as enzyme inhibitors. The nasal absorption of AVP and 1-d-8-DAVP was evaluated by measuring its antidiuretic effect. Nasal administration of AVP (0.005 IU/kg) or 1-d-8-DAVP alone (2.5 ng/kg) produced a small antidiuretic effect. Coadministration with aprotinin (1000 and 10000 KIU/kg) or soybea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Camostat, the MASP inhibitor, has been known to improve the absorption of peptides, such as insulin, vasopressin, and calcitonin, through the epithelial sheets of the nasal mucosa, skin, and intestinal mucosa ( Morimoto et al, 1991 , 1992 ; Yamamoto et al, 1994 ; Tozaki et al, 1998 ). The improved absorption has been understood to be due to the prevention of peptide degradation by endogenous proteases, but inhibition of the dynamic repair mechanism of barrier function by MASP-mediated proteolysis may also contribute to the improved permeability and absorption of peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Camostat, the MASP inhibitor, has been known to improve the absorption of peptides, such as insulin, vasopressin, and calcitonin, through the epithelial sheets of the nasal mucosa, skin, and intestinal mucosa ( Morimoto et al, 1991 , 1992 ; Yamamoto et al, 1994 ; Tozaki et al, 1998 ). The improved absorption has been understood to be due to the prevention of peptide degradation by endogenous proteases, but inhibition of the dynamic repair mechanism of barrier function by MASP-mediated proteolysis may also contribute to the improved permeability and absorption of peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These results reflect the results of in situ closed loop experiments. [17][18][19] In this study, the hypoglycemic effects observed after oral administration of insulin were increased by these protease inhibitors. 4,8 Therefore, we consider that the absorptionenhancing action of sodium glycocholate was more predominant for improving insulin absorption from the colon than its protease inhibitory activities in this study.…”
Section: Discussionmentioning
confidence: 81%
“…鼻黏液和鼻黏膜的多种代谢酶可形成“酶屏障”,降低药物活性,故处方中常添加蛋白酶和肽酶抑制剂等以避免药物降解 [ 57 ] 。如抑肽酶、氨肽酶或亮肽与鲑降钙素联合使用时,可增强降钙素的鼻吸收;杆菌肽和嘌呤霉素等可用于阻断亮氨酸脑啡肽和人生长激素等药物的酶降解 [ 58 ] 。此外,一些吸收促进剂也能实现酶抑制,如乙烯二胺四乙酸二钠可减少β片层阻断肽在鼻腔的酶降解 [ 59 ] 。…”
Section: 提高药物经鼻递送效率的策略unclassified